The relationship between demographic variables, perceptions of Diversity Climate and Key Performance Indicators: Evidence from an East-Midlands based local authority. - Williams, Aoife (2022)
The present study reports on the results from a survey which examined the relationship between demographic characteristics, perceptions of Diversity Climate, and Key Performance Indicators (Job Satisfaction, Organisational Commitment, Turnover Intention, and Meaningfulness at Work) of 232 employees within an East-Midlands based local authority. Social Identity Theory and The Interactional Model of Diversity are utilised to explore the relationship between demographic variables and perceptions of Diversity Climate, the relationship between perceptions of Diversity Climate and Key Performance Indicators, as well as the relationship between demographic characteristics and Key Performance Indicators. A multiple regression model revealed a significant relationship between Perceptions of Diversity Climate, Job Satisfaction and Organisational Commitment. Furthermore, the analysis revealed that those on fixed-term contracts had higher perceptions of Diversity Climate than permanently contracted employees; Those employed for over 15 years at the organisation had higher commitment than those who had been employed for 11-14 years, and there were significant differences in Job Satisfaction between Departments of the organisation. As well as this, women had significantly higher Job Satisfaction than men; Younger employees had higher turnover intentions than older employees; Full-time workers had higher turnover intentions than part-time workers; Women had higher Meaningfulness at Work scores than Men; and Heterosexual employees had higher Meaningfulness at Work scores than LGBTQ employees. This article discusses the limitations of the present study, as well as the theoretical and practical implications of these findings for future research.